Batik Wastewater Treatment: Performance of Combination PAC with Hydrocyclone Separation - Rosariawari, Firra; Amalia, Aussie; Dienullah, R Mohammad Alghaf; Fauzianto, Fajar Shufi; Rizqa, Fauzul (Universitas Diponegoro, 2026)
Batik wastewater contains high levels of total suspended solids (TSS) and turbidity, making it difficult to decompose naturally. To prevent environmental pollution, this study investigated a treatment method that combined coagulation in a mixing tank and flocculation using a hydrocyclone. Polyaluminum chloride (PAC) was used as the coagulant. The coagulation process was tested at stirring speeds of 100–140 rpm and coagulant doses of 150–300 mg/L. The results showed that a coagulant dose of 300 mg/L and a stirring speed of 140 rpm achieved the highest removal efficiencies: 95.45% for TSS and 95.24% for turbidity. A two-way analysis of variance (ANOVA) confirmed that the coagulant dose significantly affected removal efficiency (p=0.049), whereas the stirring speed did not have a significant effect (p=0.77). Furthermore, particle size analysis (PSA) and zeta potential tests indicated that the PAC coagulant successfully destabilized the suspension in the wastewater, leading to the formation of large aggregates and accelerating the separation process. Overall, these results indicate that combining a coagulation mixing tank with a hydrocyclone flocculation unit offers an efficient and rapid solution for treating batik wastewater.